Sultines as o-Quinodimethane Precursors in an Oxa-Diels–Alder Reaction: Synthesis of Functionalized Isochromans - Ngamnithiporn, Aurapat; Chuentragool, Padon; Songthammawat, Poramate; Punnita, Supakarn; Photong, Kittithuch; Ploypradith, Poonsakdi; Ruchirawat, Somsak (Synlett, 2024)
The development of an oxa-Diels–Alder reaction between sultines and carbonyl compounds is reported. o-Quinodimethanes, generated from sultines, undergo a [4+2]-cycloaddition with activated aldehydes or ketones in the presence of Cu(OTf)2 to provide a variety of functionalized isochromans, including spiroisochromans, in up to 99% yield. The developed protocol demonstrates broad functional-group compatibility and tolerates unprotected isatins bearing free NH-functionalities.
Keywords: quinodimethanes; oxa-Diels–Alder reaction; cycloaddition; sultines; isochromans